2022
DOI: 10.1017/s0033291721004694
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the severity and natural recovery of child PTSD symptoms: a longitudinal analysis of children exposed to acute trauma

Abstract: Background Higher levels of PTSD symptoms are present among trauma-exposed females v. males in adulthood; however, much less is known about the emergence of this sex difference during development. Methods In a multi-study sample of 7–18-year-olds (n = 3397), we examined the effect of sex and age on the severity of PTSD symptoms after a single incident trauma at 1 month (T1), and on symptom change after a natural recovery period of 3 (T2) and 6 months (T3). PTSD scores were harmonised acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…In children, a meta-analysis investigating PTSD prevalence and symptom severity in the first 12 months post-trauma concluded that there was a period of spontaneous recovery in the initial 3–6 months post-trauma, with only small improvements seen after this point (Hiller et al, 2017 ). These findings are similar to results from a multi-study sample of 7–18-year-olds, in which a natural 25% decline in child PTSD symptoms was observed at 3 months, with little improvement thereafter (Hiscox et al, 2022 ). In the adult literature, a systematic review of longitudinal studies between 1998 and 2010 found the median prevalence of PTSD in adults exposed to trauma to be 28.8% at 1 month, declining to 17% at 12 months, with most evidence of changes in median prevalence within the first 6 months (Santiago et al, 2013 ).…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…In children, a meta-analysis investigating PTSD prevalence and symptom severity in the first 12 months post-trauma concluded that there was a period of spontaneous recovery in the initial 3–6 months post-trauma, with only small improvements seen after this point (Hiller et al, 2017 ). These findings are similar to results from a multi-study sample of 7–18-year-olds, in which a natural 25% decline in child PTSD symptoms was observed at 3 months, with little improvement thereafter (Hiscox et al, 2022 ). In the adult literature, a systematic review of longitudinal studies between 1998 and 2010 found the median prevalence of PTSD in adults exposed to trauma to be 28.8% at 1 month, declining to 17% at 12 months, with most evidence of changes in median prevalence within the first 6 months (Santiago et al, 2013 ).…”
Section: Introductionsupporting
confidence: 88%
“…Several theories have been proposed to explain the higher prevalence of PTSD following intentional trauma, including higher levels of distress during the trauma (Ozer, Best, Lipsey, & Weiss, 2003 ), increased negative beliefs (Christiansen & Hansen, 2015 ), and loss of social support (Jiang, Webster, Robinson, Kassam-Adams, & Richmond, 2018 ). There is also evidence that the type of exposure can lead to different symptom manifestations (Birkeland et al, 2021 ) and influence the course of PTSD, with some studies reporting that intentional trauma is associated with poorer recovery (Hiscox et al, 2022 ; Santiago et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…39,40 With regard to the effect of sex assigned at birth on the increase and maintenance of PTSD symptoms, some studies suggest that these differences begin to appear after the age of 12 years. 41 In particular, children and adolescents experiencing a sexual violence event, hostage situation, or terrorist attack are at risk of PTSD in more than 50% of cases, 30,34,42 whereas the ones experiencing natural disasters are approximately 30%. 43 Moreover, a growing literature is examining age-specific clinical features and the necessity of developing child-focused interventions.…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies found no effect of sex assigned at birth in the development of PTSD . With regard to the effect of sex assigned at birth on the increase and maintenance of PTSD symptoms, some studies suggest that these differences begin to appear after the age of 12 years . In particular, children and adolescents experiencing a sexual violence event, hostage situation, or terrorist attack are at risk of PTSD in more than 50% of cases, whereas the ones experiencing natural disasters are approximately 30% .…”
Section: Introductionmentioning
confidence: 99%
“…Christiansen & Hansen, 2015 ; Olff, 2017 ; Olff et al, 2007 ) across the life span (e.g. Grenier et al, 2019 ; Hiscox, Bray, et al, 2023 ; Rezayat et al, 2020 ). PTSD, for instance, is typically two to three times more common in women than in men (Tortella-Feliu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%